Cost Analysis of Metallic Stents for Chronic Ureteral Obstruction: A Multicenter Study. Issue 1 (January 2017) - Frederick, Luke; Ellimoottil, Chad; Kadlec, Adam; Shah, Arpeet; Turk, Thomas; Schwartz, Bradley F.
Abstract : Introduction: : Metallic and polymer ureteral stents are used to manage chronic ureteral obstruction. In general, metallic stents are more costly than polymer stents but they are changed less frequently. We examined the overall costs of using these stent types at 2 institutions. Methods: : We identified all patients in whom a metallic stent was placed at 2 academic institutions between July 2007 and July 2013. We calculated the average time to stent exchange or failure and the overall cost of metallic and polymer stent use. Costs included those associated with materials, operating room services, anesthesia and other expenses. Results: : We identified 86 patients in whom a total of 230 metallic stents were placed. Time to stent failure or exchange of a metallic stent was 7.4 months. The per unit cost of a polymer stent and a metallic stent was 121 and 887, respectively. The average annual cost of unilateral and bilateral metallic stents was 7, 859.43 and 9, 296.37, respectively. For a unilateral polymer stent that was changed every 3 months the yearly cost was 16, 342. For bilateral polymer stents that were changed every 3 months the cost was 16, 826 per year. If unilateral and bilateral polymer stents were changed every 6 months, the costs were 8, 171 and 8, 413, respectively. Conclusions: : Our findings suggest that because metallic stents are changed less frequently than polymer stents, the annual expense associated with treating patients with chronic ureteral obstruction can be decreased by using metallic stents.